Funktioner som försvann: det kontrastiva perspektivet i äldre svensk lexikografi - Hannesdóttir, Anna Helga (Nordiske Studier i Leksikografi, 2001)
This article deals with the contrastive perspective in Swedish lexicography in the 19t century. The first complete monolingual dictionary of Swedish, published 1850-1855, dependshlargely on theh bilingual tradition that had been developed during the 18t and early 19t century. In spite of this, it does not exhibit any traces of a contrastive perspective. In the two monolingual fragments, Kindblad 1840[-41] and Almqvist 1842[-44], on the other hand, a contrastive analysis is central to the lexical description of the headwords. In fact, the fragments demonstrate a very different and theoretically advanced lexical analysis compared to the succeeding monolingual dictionaries of Swedish.